The San Antonio Sodium Reduction Initiative: Lessons Learned and Recommendations. Issue 3 (4th May 2019) - Sosa, Erica T.; Ullevig, Sarah L.; Spitsen, Ellen; Heine, Anne; Perez, Casey; Shields, Kathleen
ABSTRACT: Background : The Sodium Reduction Initiative (SRI), a voluntary collaboration among the local health department and community partners, aimed to reduce sodium in worksites and federally funded meal programs throughout Bexar County.Purpose : The purpose of this study was to assess sodium-related purchasing, preparation, and policies among food providers before and after the SRI and identify factors impacting implementation.Methods : Sodium-related practices and policies were assessed using the Sodium Practices Assessment Tool (SPAT). Stakeholder interviews were conducted to identify factors impacting initiative implementation.Results : SPAT data revealed increased healthy practices in worksites after SRI, including using recipes and measuring salt during food preparation. Qualitative analysis of interviews revealed that implementation was facilitated by the SRI team's expertise; existing health initiatives; and an organizational culture of wellness but impeded by concerns regarding customer dissatisfaction with lower sodium items; lower sodium ingredient availability and expense; and time constraints.Discussion : Organizations interested in implementing similar initiatives might consider embedding efforts into existing health initiatives; establishing organizational networks to share resources; and providing new partners with evaluation assistance.Translation to Health Education Practice : Health Educators can educate foodservice providers on the importance of sodium reduction as well as develop and evaluate sodium reduction initiatives.